THE IMPACT OF TECHNOLOGICAL GROWTH ON SOCIAL CHANGE AMONG MOTHERS IN THE VILLAGE OF AEK HITETORAS DISTRICT MARBAU DISTRICT NORTH LABUHAN BATU - Nilam Sari Pakpahan; Ali Akbar (SANGKéP: Jurnal Kajian Sosial Keagamaan, 2024)
This journal was written to find out how social change among mothers in Aek Hitetoras Village, Marbau District, North Labuhanbatu Regency, is affected by technological advancements. The research used is qualitative with a descriptive approach and observation and interview data collection methods. In this study, data analysis includes data reduction, data display, and drawing conclusions. Mechanical improvements manily affect parts of life, so it frequently sets off rubbing among society, including among moms. People's lives and patterns of interaction are impacted in both positive and negative ways by the friction caused by technological advancements. The findings of the research lead us to the conclusion that technological advancements have both positive and negative effects on society.